Assessment of Physicochemical Quality of Abattoir-Effluent Impacted Iyi-Etu River and other Water Sources at the Amansea Livestock Market Settlement, Anambra State, Nigeria - G.K. Nfor; V.N. Chigor; M.O. Emurotu; I.I. Ibangha; L.I. Ezeogu (Journal of Applied Sciences and Environmental Management, 2022)
The pollution load and anthropogenic pressure on different water sources may be reflected in the physicochemical quality evaluation of drinking water sources. This study was undertaken to evaluate the physicochemical quality of the Iyi-Etu River and other water sources such as well and borehole used by the Amansea livestock market settlement for drinking and domestic purpose. A total of 96 (36 river, 12 well, 12 borehole, 12 effluent, and 24 sachet water samples) samples were collected from these sources over 12 months. The water samples were collected using a composite sampling technique and temperature, pH, electrical conductivity, and total dissolved solids were measured onsite in triplicates using a water quality meter. Temperature, pH, electrical conductivity, and total dissolved solids recorded in this study ranged as follows: 23.8-32.6 ˚C, 5.2-8.6, 3.9×101 to 3.8×103 µS/cm and 1.9×101 to 1.9×103 mg/L respectively. The mean pH and temperature of all sample types were within WHO standard guidelines for drinking water. All sample types except well and effluent samples were within the limit of WHO guidelines for electrical conductivity of drinking water. Measurements of EC and TDS were lower upstream (112.2 µS/cm; 56.5 mg/L) than downstream 1 (203.3 µS/cm; 108.2 mg/L) and downstream 2 (197.1 µS/cm; 98.1 mg/L). These figures reveal the possible contamination of the Iyi-Etu River with abattoir effluent coming from the Amansea abattoir that is near the river. The Iyi-Etu River and well water are contaminated with different sources of contamination and serve as a public health hazard to all those using it for drinking and or domestic purposes.